Diversity In the Training of Specific Skills, Educational Management Strategy in Rural Areas, Examples of Good Practices - Angelica MUSAT; Constanta Laura ZUGRAVU; Ciprian GRIGORESCU; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2022)
The present research propose to analyze the diversity in the training of specific skills methodology which consists of a set of processes, which are distinct but somehow related coherent, to guide the articulation of initiatives in local development as well as the identification and implementation of creative possibilities of income. Starting with the institutional provisions and planning across organizations partners at national and local levels, these processes aim to systematically identify opportunities job creation and income at the community level community /local; to design and implement appropriate training programs; and to provide the support needed after the training, for example, a access to markets.
Keywords: motivation; educational management